Intraoperative Resting-State Functional Connectivity Based on RGB Imaging - Charly Caredda; Laurent Mahieu-Williame; Raphaël Sablong; Michaël Sdika; Fabien C. Schneider; Jacques Guyotat; Bruno Montcel (Diagnostics, 2021)
RGB optical imaging is a marker-free, contactless, and non-invasive technique that is able to monitor hemodynamic brain response following neuronal activation using task-based and resting-state procedures. Magnetic resonance imaging (fMRI) and functional near infra-red spectroscopy (fNIRS) resting-state procedures cannot be used intraoperatively but RGB imaging provides an ideal solution to identify resting-state networks during a neurosurgical operation. We applied resting-state methodologies to intraoperative RGB imaging and evaluated their ability to identify resting-state networks. We adapted two resting-state methodologies from fMRI for the identification of resting-state networks using intraoperative RGB imaging. Measurements were performed in 3 patients who underwent resection of lesions adjacent to motor sites. The resting-state networks were compared to the identifications provided by RGB task-based imaging and electrical brain stimulation. Intraoperative RGB resting-state networks corresponded to RGB task-based imaging (<semantics>DICE:0.55<mspace width="3.33333pt"></mspace>±<mspace width="3.33333pt"></mspace>0.29</semantics>). Resting state procedures showed a strong correspondence between them (<semantics>DICE:0.66<mspace width="3.33333pt"></mspace>±<mspace width="3.33333pt"></mspace>0.11</semantics>) and with electrical brain stimulation. RGB imaging is a relevant technique for intraoperative resting-state networks identification. Intraoperative resting-state imaging has several advantages compared to functional task-based analyses: data acquisition is shorter, less complex, and less demanding for the patients, especially for those unable to perform the tasks.